Comparison of NGS panel and Sanger sequencing for genotyping CAG repeats in the AR gene. Issue 6 (25th March 2020) - Rocca, Maria Santa; Ferrarini, Margherita; Msaki, Aichi; Vinanzi, Cinzia; Ghezzi, Marco; De Rocco Ponce, Maurizio; Foresta, Carlo; Ferlin, Alberto
Abstract: Background: The androgen receptor (AR) is a nuclear receptor, encoded by the AR gene on the X chromosome. Within the first exon of the AR gene, two short tandem repeats (STR), CAG and GGC, are a source of polymorphism in the population. Therefore, high‐throughput methods for screening AR, such as next‐generation sequencing (NGS), are sought after; however, data generated by NGS are limited by the availability of bioinformatics tools. Here, we evaluated the accuracy of the bioinformatics tool HipSTR in detecting and quantify CAG repeats within the AR gene. Method: The AR gene of 228 infertile men was sequenced using NGSgene panel. Data generated were analyzed with HipSTR to detect CAG repeats. The accuracy was compared with the results obtained with Sanger. Results: We found that HipSTR was more accurate than Sanger in genotyping normal karyotype men (46, XY), however, it was more likely to misidentify homozygote genotypes in men with Klinefelter syndrome (47, XXY). Conclusion: Our findings show that the bioinformatics tool HipSTR is 100% accurate in detecting and assessing AR CAG repeats in infertile men (46, XY) as well as in men with low‐level mosaicism. Abstract : HipSTR was used as bioinformatics tool to detect CAG repeats. HipSTR genotyped men with normal karyotype (46, XY) with a higher accuracy compared with Sanger.